Transparency and accountability in the legal framework governing the upstream hydrocarbon industry in Tanzania mainland - Mushi, Shirley Baldwin (Department of Public Law, 2021)
It is widely believed that the slow socio-economic development of resource rich countries may be curbed by the promotion of transparency and accountability in resource governance. There is a universal consensus among politicians, multilateral institutions, corporations, and civil societies that the ‘paradox of plenty' and its associated social ills of corruption, poverty and conflict are mainly due to the lack of transparent and accountable resource governance. Nations have thus adopted policies and legal frameworks on resource governance that seek to codify and implement the principles of transparency and accountability. Even so, transparency and accountability are still far from being realised in most developing nations. This thesis argues that transparency and accountability may only be realised in practice if their aspects are duly incorporated in the law. Using the conceptual foundations on the governance principles of transparency and accountability, the thesis identifies four components that a legal framework ought to incorporate to foster transparency and accountability in practice. First, there has to be clear provisions establishing accountability relationships in the legal framework. Questions on who the actors are, who is to be called to account, who is entitled to hold another to account, and for what could one be held accountable have to be made very clear in the law. Even within the framework of multiple accountability mechanisms clarity of the circumstance the various mechanisms function is key. Equally, transparency relationships have to be clear on the kind and nature of the information to be disclosed, to whom it may be disclosed, at what time and in which manner such information may be disclosed. Second, the legal framework must provide for suitable accountability implementation mechanisms that give the accountor the required independence and mandate to inquire, render judgment and have the capacity to put its decisions to effect. Third, the legal framework ought to be able to create a well-coordinated web of accountability structures to provide for checks and balances. The legal framework should be able to ensure that actors given authority to fulfil their obligations are able to answer and face vigorous scrutiny and verification processes by independent actors. Lastly, the legal framework has to facilitate access to clear, reliable and complete information by interested parties and the public to promote transparency. The thesis uses these components to conduct an appraisal of the legal and institutional framework governing hydrocarbons in Tanzania. It establishes whether the governance aspects of transparency and accountability are duly incorporated in the legal framework to ensure their implementation in practice. It concludes that Tanzania's legal framework on hydrocarbons recognises on paper the value of transparency and accountability, but it largely fails to incorporate them sufficiently in a way that ensures they are fully implemented.